21st birthday party for Chris Bell in the Helen O'Shea collection of Australian folklore in its social context, 1989-1990 - Bell, Chris, 1968-; O'Shea, Helen (1989)
Folkloric recording. Conversation: Stuart Drake talks about his business Duck Rock Mobile Disco. Party: Bill McKinnon announces supper and the speeches; Basil Lee proposes a toast to Chris; singing For He's a Jolly Good Fellow; John Bell, Chris's father, presents the key to Chris; Chris Bell thanks his family and guests; singing Happy Birthday.
Recorded by Helen O'Shea.
Part of a collection of recordings made by Helen O'Shea in the township of Ecklin South, Victoria in 1989 and 1990. The recordings aim to reveal the social fabric of life in a small rural community between 1900 and 1988.
Recorded at the Ecklin Hall, Ecklin South, Vic. on 12 August 1989.
Digital master available
Keywords: Entertaining -- Victoria -- Ecklin South; Ecklin South (Vic.) -- Social life and customs